Acoustic toys and buzzing tops from Corinth. On two unpublished ludic objects at Geneva (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2022)
The paper deals with two unpublished ludic objects, made of clay, on display at the Musée d’Art et d’Histoire of Geneva (CH). Clearly, the first item is a ball-shaped rattle. More challenging is the interpretation of the second one, whose elegant decoration let it be compared to Corinthian pottery between Late Protocorinthian Period and Early Corinthian. The Author proposes it should be interpreted as a spinning top. Both ludic artefacts have evocative visual and acoustic effects.
Keywords: ludus, toy, spinning top, rattle, Corinthian pottery, Corinth